Colonoscopy and sigmoidoscopy use among the average-risk population for colorectal cancer: a systematic review and trend analysis - Cardoso, Rafael; Hoffmeister, Michael; Brenner, Hermann (Cancer Prevention Research, 2019)
Monitoring population-level colonoscopy and sigmoidoscopy use is crucial to estimate the future burden of colorectal cancer and guide screening efforts. We conducted a systematic literature search on colonoscopy and sigmoidoscopy use, published between November 2016 and December 2018 in the databases PubMed and Web of Science to update previous reviews and analyze time trends for various countries. In addition, we used data from the German and European Health Interview Surveys and the National Health Interview Survey to explore recent time trends for Germany and the US, respectively. The literature search yielded 23 new articles: fourteen from the US and nine from Australia, Canada, England, Germany, Saudi Arabia, and South Korea. Colonoscopy use within 10 years was highest and, apart from the youngest age groups eligible for colorectal cancer screening, kept increasing to levels close to 60% in the US and Germany. A recent steep increase was also observed for South Korea. Limited data were available on sigmoidoscopy use; regional studies from the US suggest that sigmoidoscopy has become rarely used. Despite high uptake and ongoing increase in the US, Germany, and South Korea, use of colonoscopy and sigmoidoscopy has either remained low or essentially unknown for the majority of countries.
Gesehen am 04.10.2019